Clinical assessment of scannographic markers for sarcopenia in lung transplant candidates. (September 2022) - Zappella, Nathalie; Vaillant, Garance; Saker, Loukbi; Kantor, Elie; Mordant, Pierre; Messika, Jonathan; Bunel, Vincent; Khalil, Antoine; Tran Dinh, Alexy; Montravers, Philippe
Abstract: Introduction: The selection of patients for lung transplantation is difficult. An aspect of the patient's general condition and frailty can be assessed by measuring the surface area of certain muscles on CT. Indeed, sarcopenia, assessed by measuring the area of psoas muscles on scannographic sections has already been shown to be associated with poor outcomes in lung transplant and other major surgeries and could thus be helpful to evaluate candidates to lung transplant. However, it is not routinely performed by radiologists. As a pilot study, we compared the reliability of computerized tomography scan assessment for sarcopenia by clinicians with that of radiologists. Materials and methods: We conducted a retrospective single-centre study in which preoperative abdominal CT scans of lung transplant patients from 2014 to 2018 were analysed to assess sarcopenia by measuring the surface areas (mm 2 ) of the psoas, paraspinal muscles at the L4 vertebra and diaphragm pillars at the celiac trunk bilaterally. The surfaces were blindly assessed by clinicians and radiologists and the intraclass correlation coefficients between the two measurements were estimated by a generalized linear model using SAS 9.4 software. Results: We performed a double reading of 200 scans. The clinicians 'measurements were comparable to those of the radiologists for the psoas and paraspinal muscles but not for the diaphragm pillars. Conclusion: CT measurement of psoas and paraspinal muscle areas by clinicians appears reliable and feasible in routine practice and could be used in the evaluation of lung transplant candidates. Highlights: Sarcopenia can be assessed by measuring the area of psoas muscles on CT scan. CT scan assessement of sarcopenia could help evaluating candidates to lung transplant. Clinician can make reliable measures of psoas and para spinal muscles on CT scan.